Digital literacy and digital didactics for the development of new learning models - Valeriy Ivanovich, Prasolov; Vladimirovich, Kabanov Oleg; Anatolievich, Grigoryev Andrey; Sergeevich, Govorkov Aleksey; Ivanovich, Shevtsov Vladimir; Nashatovna, Minsabirova Venera; Vladimirovna, Yakovenko Nataliya (Opción, 2020)
The study aims to investigate digital literacy and digital didactics as the basis for the development of new learning models via comparative qualitative research methods. As a result, the principle of personalization implies the ability of a student to independently determine the purpose of training, choose a strategy for the educational process, the pace and level of development of the educational program. In conclusion, to determine digital literacy, an index was developed which shows how prepared the teacher is for learning online and through innovation.